Intestinal parasitic infections: telephone health literacy with men in areas of poverty in the syndemic - Julio Cesar Pegado Bordignon; Antonia de Castro Ribeiro; Érica Tex Paulino; Maria de Fatima Leal Alencar; Marcio Neves Boia; Antonio Henrique Almeida de Moraes Neto (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to assess Popular Health Education practices on intestinal parasites, carried out by telephone contact with men living in urban communities in Rio de Janeiro, Brazil, during the COVID-19 syndemic. Method: a quasi-experimental, quantitative and descriptive study, carried out with men aged 20 to 59 years. Pre-test was applied, and participants were divided into two groups: control and experimental. Popular Education in Health practices were carried out with an experimental group, and post-test was applied for both. Results: health education practices were significant in the experimental group, with a reduction in incorrect answers. There was an increase in incorrect answers in the control group's post-test. Conclusions: the Brazilian National Policy for Popular Education in Health contributed to qualify men's health literacy on intestinal parasites. Practice by telephone contact proved to be a powerful strategy for nursing and public policies to access this group and promote health in Primary Health Care.